Strength of Religious Faith in Peruvian Adolescents and Adults: Psychometric Evidence from the Original and Short Versions of the Santa Clara Strength of Religious Faith Questionnaire in Spanish - Caycho-Rodríguez, Tomás (Pastoral psychology, 2022)
The aim of this study was to evaluate the psychometric evidence of the original and short versions of the Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) in Spanish in a sample of 245 Peruvian adolescents and adults (mean age = 21.04 years, SD = 3.07, 47.8% male and 52.2% female), selected by nonprobabilistic convenience sampling. Additionally, the Coronavirus Anxiety Scale and the Satisfaction with Life Scale were applied. Confirmatory Factor Analysis, internal consistency reliability methods, hierarchical sequence of variance models, and a graded response model were used. Results indicate that both versions of the SCSRFQ showed robust psychometric properties: adequate unidimensional structure, adequate difficulty and discrimination parameters, and significant relationships with the measures of fear of COVID-19 and satisfaction with life. The original version of the SCSRFQ showed evidence of strict measurement invariance by sex and age, whereas the short version showed strict invariance by sex and configural invariance by age. Both versions showed acceptable reliability indices. In conclusion, the original and short versions of the SCSRFQ in Spanish show evidence of psychometric indicators that support their use to assess the strength of religious faith.